2010
DOI: 10.1177/1557988310373944
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity as a Factor in Reproductive Health Care Utilization Among Males Attending Family Planning Clinics

Abstract: Health care utilization of reproductive health care services among males is an emerging issue. This study examined ethnicity as a factor in reproductive health care utilization among 1,606 African American and Hispanic young males attending family planning clinics. Seventy percent were African American and 30% were Hispanic. Across groups, the most received service was treatment for a sexually transmitted infection (STI). African American males were more likely than Hispanic males to have health insurance, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In this review, lack of health insurance (defined as having no insurance, no health care, or no public or private health insurance coverage) proved to be a primary barrier for young Black males accessing SRH-preventive services (Buzi & Smith, 2014; Conserve et al, 2017; Goyal et al, 2014; Weinman et al, 2011). A prominent reason for not accessing SRH services in clinics appeared to be financial, including the cost of clinic visits and lack of alternative fee structures (e.g., sliding scale) for clinic services.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In this review, lack of health insurance (defined as having no insurance, no health care, or no public or private health insurance coverage) proved to be a primary barrier for young Black males accessing SRH-preventive services (Buzi & Smith, 2014; Conserve et al, 2017; Goyal et al, 2014; Weinman et al, 2011). A prominent reason for not accessing SRH services in clinics appeared to be financial, including the cost of clinic visits and lack of alternative fee structures (e.g., sliding scale) for clinic services.…”
Section: Resultsmentioning
confidence: 97%
“…A prominent reason for not accessing SRH services in clinics appeared to be financial, including the cost of clinic visits and lack of alternative fee structures (e.g., sliding scale) for clinic services. Those with nonprivate insurance (e.g., Medicaid or uninsured) were reported to be less likely to undergo gonorrhea and chlamydia testing (Buzi & Smith, 2014; Goyal et al, 2014; Weinman et al, 2011). Lack of knowledge was also a persistent theme (Boyd et al, 2018; Buzi & Smith, 2014; Goyal et al, 2014; Pastuszak et al, 2017; Ricks et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study, conducted among males aged 16-28 in a family planning clinic, indicated that few (5%) were interested to learn more about birth control. 19 However, another clinic-based study conducted among male patients aged 16-35 found that the majority wanted their healthcare provider to bring up family planning topics including how to use a condom correctly (70%), female birth control methods (64%), and emergency contraception (75%). 18 The findings of the current study extends this literature by assessing young men’s perceptions of having learned about pregnancy prevention, rather than just their interest in the topic, and the importance of addressing care beyond a focus on just STDs/HIV.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although the majority of young men are seen in primary care, [14][15][16] past clinic-based studies have been conducted in family planning settings and focus on young men's attitudes and behaviors toward contraception use, rather than pregnancy prevention service receipt. [17][18][19] Data about pregnancy prevention service receipt from nationally representative household-based samples of young men have not typically differentiated between the clinical settings where such services are delivered (eg, primary care, family planning, or sexually transmitted disease [STD] clinics) and highlight that less than one quarter of young men report pregnancy prevention service receipt in the last year. 1,20 Research on pregnancy prevention in clinical settings has typically focused on sexually active young men and does not typically include young men who may be on the brink of sexual activity.…”
Section: Introductionmentioning
confidence: 99%